Violence Against Junior Medical Doctors; Triggers and Problems of Under-Reporting - Al Mousawi, Ali M; Lafta, Riyadh K (The Malaysian Journal of Nursing (MJN), 2025)
Background: The prevalence of workplace violence has reached about two-thirds of healthcare workers being exposed, and this problem is rising globally. It varies across different geographical regions, with different triggering factors. Objective: To identify the triggers of violence against healthcare workers in Iraqi health facilities. Methods: A sample of 1,079 Iraqi junior doctors from 18 secondary hospitals was surveyed between August 2021 and January 2022 using a semi-structured questionnaire to determine the reasons behind this problem. Results: The main triggers reported by the respondents were a shortage of medicines (16.9%), aggressive attitudes of patients’ relatives (15.4%), patient death (10.4%), and workload (7.8%). Other factors included poor hospital security and inadequate protective measures. An important issue raised was the high proportion of underreporting violent incidents, with reasons including feelings of shame, the perception that such attacks are part of the usual daily routine, and a belief that reporting will not improve their work environment. Some respondents also felt that reporting would result in their blame or punishment. Conclusion: Shortages of supplies and poor healthcare services play a major role in provoking violence. As a future course of action, improving healthcare quality, staff training, the implementation of strict legislation, and the establishment of guidelines to encourage reporting could help reduce violence in healthcare settings.